Atlas : the ultimate guide to the world - Watson, Malcolm; Carpenter, Clive (San Diego, California Silver Dolphin Books, 2007)
"Experience the world in a whole new way with this modern atlas. Discover amazing facts and statistics about the countries of the world. Explore the up-to-date maps on every page. Includes two large posters of the world and North America."--Cover back.
Posters -- North America -- South and Central America -- Europe -- Africa -- Asia -- Oceania
Cover title
Includes index
Keywords: Atlases; Geography